Characteristics of acquisitions in the Central and Eastern European economies in transition - Matej Lahovnik (Management : Journal of Contemporary Management Issues, 2000)
This paper deals with strategic issues of acquisitions in Central and Eastern European economies in transition: Slovenia, the Czech Republic, Hungary, Croatia and Poland. The underlying motives for 45 acquisitions in Slovenia and 11 acquisitions in other Central and Eastern European economies are identified and compared together with certain characteristics of the acquisition process. This study also identifies the motives of the owners of target companies in agreeing to sell. There are only two hostile take-overs in the samples under study. Therefore, the motives of the target companies’ managers in supporting sales are of special interest in this paper. The performance of the acquired companies is measured against the realisation of the key motives.